Determinants of borrowers' default in P2P lending under consideration of the loan risk class - Michal Polena; Tobias Regner (Friedrich Schiller University Jena, 2016)
We study the determinants of borrowers' default in P2P lending with a new data set consisting of 70,673 loan observations from Lending Club. Previous research identified a number of default determining variables but did not distinguish between different loan risk levels. We define four loan risk classes and test the significance of the default determining variables within each loan risk class. Our findings suggest that the significance of most variables depends on the loan risk class. Only few variables are consistently significant across all risk classes. The debt-to-income ratio, inquiries in the past 6 months and a loan intended for a small business are positively correlated with the default rate. Annual income and credit card as loan purpose are negatively correlated.
Keywords: D14; E41; G23; 330; crowdfunding; peer-to-peer lending; P2P; credit grade; FICO score; default risk